The identity of Pilumnoplax acanthomerus Rathbun, 1911 (Crustacea: Decapoda: Brachyura: Xanthidae), with new records from the central and western Pacific - Mendoza, Jose Christopher E.; Clark, Paul F.; Ng, Peter K. L. (Zootaxa, 2012)
The identity of the rare xanthid crab, Pilumnoplax acanthomerus Rathbun, 1911, originally described from the AmiranteIslands in the western Indian Ocean, is elucidated. Števčić (2005) transferred the species from Pilumnoplax Stimpson,1858, to a new genus, Linnaeoxantho. This monotypic genus is re-diagnosed and new morphological characters are high-lighted. New records from Ryukyu and Line Islands, in the western and central Pacific, respectively, are reported. Linnae-oxantho is compared with the morphologically similar Melybia Stimpson, 1871, from the western Atlantic, and theiraffinities are discussed. Linnaeoxanthinae Števčić, 2005, is here recognised as a valid xanthid subfamily for Linnaeoxantho and Melybia, and is considered to have priority over Melybiidae Števčić, 2005.